Mercury Levels in Soil, Leafy Plants and Irrigation Well Water at Several Agricultural Fields in Baghdad Government, Iraq - Abd Ali, Shaimaa Salim; Mahmood, Mahmood Basil (Iraqi Journal of Science, 2019)
Soil and plant contamination with heavy metals is one of the current problems in the world especially contamination with mercury. Heavy metals are very harmful because of their long biological half-lives, non-biodegradable nature and their possibility to accumulate at different body parts. Soil, well water and leafy plant samples (Apium graveoleus, Allium ampeloprasum, Lepidium sativum, Eruca sativa, Petroselinum hortense, Ocimum basilicum , Mentha pulegium) from three different agricultural fields (AL-Musafer village (site 1), AL-Autaifiyah (site 2) and AL-Huriyah (site 3)) in Baghdad government, Iraq were analyzed for mercury concentration. Hg level in soil samples ranged from 3.67 to 5.33 ppm in AL-Autaifiyah and AL-Musafer village, respectively. While, in water samples Hg level ranged from 1.2 in AL-Autaifiyah to 22.8 mg/l in AL-Musafer village. Plant samples recorded Hg level ranged from 0.009 to 2.88 ppm in AL-Autaifiyah and AL-Huriyah, respectively. The results showed that Hg level in water samples and most plant samples were above the acceptable limit according to WHO (1993), and FAQ/WHO (1999) respectively. While Hg level in soil samples was within the acceptable limit put by Ministry of the Environment, Finland (2007).